The mediating role of aging attitudes between social isolation and self-neglect: a cross-sectional study of older adults living alone in rural China - Yuling Jia; Yuexue Yue; Yu Sheng (BMC Nursing)
Abstract Background Self-neglect is a significant global public health issue, compromising the health, safety, and well-being of older adults. Despite extensive research on the prevalence and risk factors of self-neglect, the underlying psychosocial mechanisms remain underexplored. Social isolation and aging attitudes have been identified as important correlates of self-neglect; however, the precise interplay between these variables, particularly the mediating role of aging attitudes, has yet to be fully examined in the context of rural older adults. Objectives This cross-sectional study aims to investigate the relationships among social isolation, aging attitudes, and self-neglect, focusing on how aging attitudes mediate the association between social isolation and self-neglect among rural older adults living alone in China. Methods Using convenience sampling, we conducted a survey from December 2022 to February 2023 among rural older adults living alone across eight cities in Guizhou Province, Southwest China. Data were gathered using the General Information Questionnaire, Attitudes to Ageing Questionnaire, Lubben Social Network Scale-6, and Scale of the Elderly Self-Neglect. Data were analyzed using SPSS 27.0 and the PROCESS macro tool. Results The scores for aging attitude, social isolation, and self-neglect among older adults living alone in rural areas were 75.00 (69.00–82.00), 16.00 (12.00–21.00), and 10.00 (8.00–14.00), respectively. Social isolation was positively associated with aging attitude (r = 0.353, P < 0.05) and negatively correlated with self-neglect (r = -0.371, P < 0.05). Self-neglect was also negatively correlated with aging attitude (r = -0.367, P < 0.05). Aging attitude partially mediated the relationship between social isolation and self-neglect among older adults living alone in rural areas, with a mediation effect of -0.077, accounting for 28.20% of the total effect. Conclusion The findings suggest that aging attitudes and social isolation among rural older adults living alone are associated with self-neglect. Furthermore, social isolation may be linked to self-neglect indirectly through its association with aging attitudes. Healthcare professionals should develop strategies to promote positive aging attitudes and enhance social networks of this vulnerable population, contributing to prevent or alleviate their self-neglect behaviours.